Physical, mechanical properties and optical dispersion in Sb2O3–-NaPO3-WO3 glasses - Agti, F. Z.; Soltani, M. T.; Santos, L. F.; Messaoudi, A.; Guesmia, N.; de Ligny, Dominique (Journal of Non-Crystalline Solids, 2022)
New glasses in the composition 60Sb2O3-(40-x) NaPO3-xWO3 (where x = 0 to 40 mol.%) were prepared using the melt quenching technique. Different physical properties were measured to explain the effect of replacing NaPO3 with WO3. Differential scanning calorimetry (DSC) measurements showed high thermal stability, with Tx-Tg ∼ 100–130 °C. Glass transition temperature, Tg increased with an increasing amount of tungsten oxide. Such increase is also observed for the measurement of density, micro hardness, and the elastic moduli (longitudinal modulus (L), shear modulus (G), bulk modulus (K), and Young's modulus (E)). However, Poissn's ratio remains practically invariant and close to 0.252 confirms the bi-dimensional structure. The insertion of WO3 reduces the optical band gap and increases the refractive index from 1.584 to 1.786 at 486.1 nm where x WO3 is from 0 to 25 (mol.%). Furthermore, the measured optical dispersion changes from low dispersion crown glass to more dispersive flint glass. Following these various results, the glasses studied prove to be potential candidates for optical devices.
CRIS-Team Scopus Importer:2021-11-19
Keywords: Abbe number; DSC; elastic property; Sb; Tungsten oxide